O Ideb e as políticas educacionais em municípios do Caparaó Capixaba - Ribeiro, Welison Carlos Loiola (2022)
TThe Basic Education Development Index (Ideb) is one of the main indicators of quality in Basic Education in Brazil and is established as a reference instrument for the elaboration of educational policies. In this context, this study analyzed how the Ideb